2018
DOI: 10.1155/2018/3169431
|View full text |Cite
|
Sign up to set email alerts
|

S-Allyl Cysteine Alleviates Hydrogen Peroxide Induced Oxidative Injury and Apoptosis through Upregulation of Akt/Nrf-2/HO-1 Signaling Pathway in HepG2 Cells

Abstract: Hydrogen peroxide (H2O2) mediated oxidative stress leading to hepatocyte apoptosis plays a pivotal role in the pathophysiology of several chronic liver diseases. This study demonstrates that S-allyl cysteine (SAC) renders cytoprotective effects on H2O2 induced oxidative damage and apoptosis in HepG2 cells. Cell viability assay showed that SAC protected HepG2 cells from H2O2 induced cytotoxicity. Further, SAC treatment dose dependently inhibited H2O2 induced apoptosis via decreasing the Bax/Bcl-2 ratio, restori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 41 publications
2
9
0
1
Order By: Relevance
“…Moreover, as shown in Figure 2, our results also demonstrated that the overexpression of HO-1 in Hep3B cells attenuated H 2 O 2 -induced ROS generation. These results supported recent studies, suggesting that the upregulation of HO-1 alleviated H 2 O 2 -induced ROS and oxidative injury in HepG2 cells [49,50], although, in this study, we did not determine whether ectopic HO-1 overexpression inhibited the apoptosis of hepatoma cells. Since a recent study indicated that IL-6 drives ROS reduction by increasing Nrf 2, a transcription activator of the HO-1 gene, expression in human islet β-cells [51], further investigations into the role of IL-6-HO-1 crosstalk in hepatoma cells, in terms of ROS synthesis, are warranted.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Moreover, as shown in Figure 2, our results also demonstrated that the overexpression of HO-1 in Hep3B cells attenuated H 2 O 2 -induced ROS generation. These results supported recent studies, suggesting that the upregulation of HO-1 alleviated H 2 O 2 -induced ROS and oxidative injury in HepG2 cells [49,50], although, in this study, we did not determine whether ectopic HO-1 overexpression inhibited the apoptosis of hepatoma cells. Since a recent study indicated that IL-6 drives ROS reduction by increasing Nrf 2, a transcription activator of the HO-1 gene, expression in human islet β-cells [51], further investigations into the role of IL-6-HO-1 crosstalk in hepatoma cells, in terms of ROS synthesis, are warranted.…”
Section: Discussionsupporting
confidence: 84%
“…It has been implied that there are four signaling cascades involved in the HO-1 expression, including p38/MAPK, PI3K/AKT, JAK/STAT, and toll-like receptor pathways [52]. IL-6 is able to activate Janus kinases (JAK), which further phosphorylate STAT1 and STAT3 [23,49]. The phosphorylation of STATs induces the nuclear translocation of STATs, which further binds to the specific binding site within the promotor areas of gene-influencing gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this finding, it has shown that SAC is capable to attenuate H 2 O 2 -induced oxidative stress and apoptosis through suppressing production of ROS and lipid peroxidation products and upregulating heme oxygenase-1 and nuclear factor erythroid 2-related factor 2 in HepG2 cells. [27] Inappropriate inflammatory reactions are also key players in liver injury subsequent to exposure to toxic agents. [8,58] LPS can mobilize hepatic Kupffer cells with excess production and release of proinflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…[20] SAC has shown a wide spectrum of beneficial properties including antiapoptotic, [21] acting as an antioxidant to counteract oxidative stress, [22,23] redox modulation, [24] and also exerting antiinflammatory effects. [25,26] Of related significance to our study, SAC could attenuate H 2 O 2 -induced oxidative damage and apoptotic changes through accentuating antioxidants signaling cascade in HepG2 cells, [27] is able to lower carbon tetrachloride-induced liver fibrosis that is partly mediated through its inhibition of inflammation and oxidative damage, [28] and could protect against fat-mediated liver dysfunction in adults. [29] Furthermore, SAC can have protective effect on chromiuminduced model of hepatotoxicity [22] and is able to ameliorate LPSinduced liver damage and to suppress release of nitric oxide (NO) and myeloperoxidase (MPO) in lung tissue due to its antioxidant capacity.…”
Section: Introductionmentioning
confidence: 95%
“…따라서 anti-apoptotic Bcl-2 family 단백질에 대한 pro-apoptotic Bax family 단백질의 균형은 내재적 세포사멸 경로를 활성화하거나 억제하는 결정 요인 으로 작용한다. 이전의 많은 연구들은 간세포에서 H2O2에 의한 세포사멸 유도가 Bcl-2/Bax 비율의 감소에 따른 cas-pases의 활성화와 관련이 있음을 보여 주었다 [42][43][44] . 이전 연…”
Section: 한편 산화적 스트레스에 의해 생성되는 과도한 Ros는unclassified